2021
DOI: 10.3390/ani11072020
|View full text |Cite
|
Sign up to set email alerts
|

Caution Is Needed When Using Niche Models to Infer Changes in Species Abundance: The Case of Two Sympatric Raptor Populations

Abstract: Despite the mounting evidence supporting positive relationships between species abundance and habitat suitability, the capacity of ecological niche models (ENMs) to capture variations in population abundance remains largely unexplored. This study focuses on sympatric populations of hen harrier (Circus cyaneus) and Montagu’s harrier (Circus pygargus), surveyed in 1997 and 2017 in an upland moor area in northwestern Spain. The ENMs performed very well for both species (with area under the ROC curve and true skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Their results indicated that the abundance deficit predicted by the triangular relationship in the first period of monitoring was positively correlated with the local population growth rate between the two periods, suggesting that HSI can be used as a proxy for carrying capacity. More recently, Regos et al (2021) observed a positive relationship between abundance and HSI, but changes in HSI did not explain temporal variation in local abundances.…”
Section: Introductionmentioning
confidence: 94%
“…Their results indicated that the abundance deficit predicted by the triangular relationship in the first period of monitoring was positively correlated with the local population growth rate between the two periods, suggesting that HSI can be used as a proxy for carrying capacity. More recently, Regos et al (2021) observed a positive relationship between abundance and HSI, but changes in HSI did not explain temporal variation in local abundances.…”
Section: Introductionmentioning
confidence: 94%